Tailored antiplatelet therapy and clinical adverse outcomes. Issue 1 (5th November 2013) - Li, Jiabei; Jian, Zhao; Song, Mingbao; Guo, Wenyun; Chen, Guozhu; Lu, Wei; Qian, Dehui; Ouyang, Jing'e; Yu, Jie; Hu, Houyuan; Jin, Jun; Wu, Xiaojing; et al.
Abstract : Objective: The clinical evidence regarding the influence of tailored antiplatelet strategy on adverse outcomes has been controversial. The aim of the study was to evaluate the significance of tailored antiplatelet therapy with respect to clinical adverse events in antiplatelet-resistant patients. Methods: Randomised studies that assess clinical relevance of personalised antiplatelet treatment in antiplatelet-resistant patients were identified through a literature search: PubMed, EMBASE, Web of Science and the Cochrane Library. The primary endpoint was the composite of death from any cause and stent thrombosis. All total clinical adverse events and bleeding complications were evaluated. Results: Data were combined across seven randomised studies comprising 12 048 subjects, of whom 3738 (31.0%) were found to be antiplatelet-resistant. Antiplatelet-resistant patients provided with tailored antiplatelet therapy showed less risk of death or stent thrombosis than those assigned conventional antiplatelet treatment (0.5% vs 2.2%; OR (95% CI) 0.25 (0.13 to 0.49), p<0.0001). A significant benefit in terms of total adverse event risk reduction was observed during follow-up for tailored vs conventional antiplatelet therapy (5.5% vs 10.0%; OR (95% CI) 0.40 (0.20 to 0.77), p=0.006). No statistical difference in bleeding complications was observed between these two groups (p=0.08). Conclusions: In the study, personalised antiplatelet treatment for antiplatelet resistance was found to be associated with less occurrence of death or stent thrombosis and the less risk of total clinical adverse events than conventional treatment, without increasing the risk of bleeding complications.